Public Wage Bills in the Middle East and Central Asia - Tamirisa, Natalia; Duenwald, Christoph (Washington, D.C. : International Monetary Fund, 2018)
Analysis of policies for managing public sector wage bills in the Middle East and Central Asia region. While some work has been done recently at the Fund on issues related to government employment and compensation, to our knowledge, this is the first study to systematically examine, with a focus on the Middle East and Central Asia region, the recent trends and drivers of public wage bills in the region and to identify key policy implications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet